Orthodontic emergencies and mental state of Chinese orthodontic patients during the COVID-19 pandemic - Shuqi Quan; Yutong Guo; Jiawei Zhou; Guanning Zhang; Ke Xing; Hongxiang Mei; Juan Li (BMC, 2021)
Abstract Background The ongoing COVID-19 pandemic postponed routine follow-up visits of many orthodontic patients, which compromised their treatment process and mental states. This study was aimed to assess orthodontic emergency occurrence and psychological states of Chinese orthodontic patients during this pandemic. Methods Orthodontic patients in China were invited to answer an anonymous online questionnaire from February 20, 2020 to March 5, 2020, when routine dental care was suspended in China. The questionnaire included self-assessment of oral hygiene and compliance, orthodontic emergencies, perceptions and feelings about COVID-19 and anxiety self-rating scale, etc. Collected data was statistically analyzed with Chi-square, independent t test and univariable generalized estimating equations regression analysis. Results A total of 1078 respondents (292 male; 786 female) from 30 provinces of China were included in this study. About one-third (33.67%) of patients reported that they encountered orthodontic problems during the pandemic. Patients with clear aligners reported fewer orthodontic problems than those with fixed appliances or removable appliances. Female patients, elder patients and patients who encountered orthodontic emergencies were more anxious than other patients. Conclusions The compliance and occurrence of orthodontic emergencies differed in patients with different orthodontic appliances. Patients with orthodontic emergencies exhibited higher anxiety states.